277 Phenotypic and genetic differences in Rambouillet lines divergently selected for reproductive rate over 50 years. (30th November 2020) - Murphy, Tom; Thomson, Jennifer M; Berardinelli, James; Roeder, Brent
Abstract: A long-term selection experiment was conducted in a Rambouillet flock from 1969 to 2017. The high (HL) and low lines (LL) were divergently selected based on a maternal reproductive index, and an unselected control line (CL) was also maintained. Adult ewe traits considered were NLB, greasy fleece weight (GFW), and body weight after fall weaning of their lambs (BW). Results indicated that NLB was greatest for HL (1.67 ± 0.01), intermediate for CL (1.48 ± 0.02), and least for LL (1.28 ± 0.01; P < 0.001). Ewe GFW was greatest for LL (3.9 ± 0.02 kg; P ≤ 0.01) but not different between HL (3.82 ± 0.02 kg) and CL (3.88 ± 0.02 kg; P = 0.08); whereas, BW was least for HL (61.7 ± 0.19 kg; P ≤ 0.01) and not different between LL (62.9 ± 0.21 kg) and CL (62.6 ± 0.25 kg; P = 0.58). Heritability was estimated to be low for NLB (0.13 ± 0.02) and moderate for GFW (0.55 ± 0.03) and BW (0.46 ± 0.04). Genetic correlations were estimated to be near zero between NLB and GFW (-0.07 ± 0.08) and NLB and BW (0.12 ± 0.08) and low between GFW and BW (0.29 ± 0.06). Trends for NLB predicted breeding value differed among all 3 lines (P < 0.01) and was positive for HL (0.012 ± 0.0002 lambs/birth year), negative for LL (-0.005 ± 0.0002), and small but positive for CL (0.002 ± 0.0002). Inbreeding rates were positive in all lines but greatest for HL (0.45 ± 0.005 %/birth year), intermediate in LL (0.37 ± 0.006), and lowest in CL (0.28 ± 0.006). Results indicated long-term phenotypic selection for reproductive rate was effective and not genetically antagonistic with wool production or mature BW.